Kant-Lexikon - Bradl, Beate; McLaughlin, Peter (De Gruyter, 2015)
Kant’s revolutionary new approach to philosophy was accompanied by the introduction of a largely novel terminology.This led to the publication of a number of commentaries, dictionaries and compendia even while he was still alive. With the Kant-Lexikon,a lexical reference gives the modern reader access tohis work on the basis of present-day editions and takes into account 20th century and contemporary research and advances in lexicology.
Enthält unter anderem Artikel von Beate Marschall-Bradl und Peter McLaughlin
Enthält die Bände 1 - 3
Gesehen am 20.04.2021
Keywords: Kant *1724-1804*; Electronic books; Wörterbuch; Kant, Immanuel; Philosophie